A Planning and Budgeting Model for Strengthening Strategic Resilience in Energy and Infrastructure Asset Management - Ebehiremen Faith Iziduh,; Olawale Olasoji,; Oluwatobi Opeyemi Adeyelu, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
This paper presents a comprehensive planning and budgeting model designed to strengthen strategic resilience in energy and infrastructure asset management. Recognizing the increasing complexity and vulnerability of critical infrastructure to natural, technological, and geopolitical disruptions, the model integrates resilience principles into traditional asset management frameworks. It emphasizes key components such as resilience assessment, dynamic risk analysis, and proactive investment guided by systems thinking and stakeholder engagement. The methodology employs multi-dimensional resilience metrics and structured decision-making processes, including multi-criteria decision analysis and scenario evaluation, to prioritize investments and optimize resource allocation. By embedding resilience into planning and budgeting, the model facilitates enhanced robustness, redundancy, resourcefulness, and rapidity, contributing to sustained infrastructure performance and societal stability. The framework is adaptable across diverse contexts, promoting transparent and informed decision-making aligned with evolving threats and fiscal constraints. This work bridges theoretical resilience concepts with practical financial planning, offering a strategic tool for advancing sustainable and resilient infrastructure management.
Keywords: Strategic resilience; asset management; energy infrastructure; budgeting model; risk assessment; decision-making